A high PSRR bandgap voltage reference with piecewise compensation. (January 2020) - Que, Longcheng; Min, Daogang; Wei, Linhai; Zhou, Yun; Lv, Jian
Abstract: This paper describes an alternative high power supply rejection ratio (PSRR) bandgap voltage reference (BGR) circuit with piecewise compensation. A proportional to absolute temperature (PTAT) current structure with high loop gain is adopted to achieve high PSRR, a current proportional to absolute temperature square (PTAT 2 ) circuit is used to implement the temperature piecewise compensate. Experimental results of the proposed BGR implemented in a 0.5 ​μm CMOS process demonstrate that a PSRR of 83 ​dB is achieved, and a temperature coefficient (TC) of 8.83 ​ppm/°C over a temperature range of 165 ​°C (−40 ​°C–125 ​°C) is realized.